2020
DOI: 10.1186/s43014-020-00037-7
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional quality of formulated complementary diet from defatted almond seed, yellow maize and quality protein maize flours

Abstract: Traditional complementary foods are mainly starchy foods with limiting nutrient quality and can be fortified using protein rich crops like almond seed. This research thus aimed at investigating the nutritional quality of the formulated complementary diet from locally available almond seeds (Prunus amygdalus), high quality protein (QPM) and yellow maize after blending into flours. The proximate and amino acid compositions, in vitro protein qualities and functional properties of the blended flours were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 48 publications
2
12
1
Order By: Relevance
“…Recently, Tanwar et al (2019) studied the effect of supplementation of wild apricot kernel flour in a rat model and reported significantly ( P < 0.05) lower TPD (72.2 ± 4.9%–83.6 ± 5.9%) for wild apricot kernel than that of control (96.4 ± 3.5%). Contrarily, Adesanmi et al (2020) reported significantly ( P < 0.05) higher true digestibility (97.6%–98%) of diet/s comprising the blends of maize and almond (70:30) flours, which could be attributed due to the least amount of antinutritional factors in fermented/processed maize flour and almond.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Recently, Tanwar et al (2019) studied the effect of supplementation of wild apricot kernel flour in a rat model and reported significantly ( P < 0.05) lower TPD (72.2 ± 4.9%–83.6 ± 5.9%) for wild apricot kernel than that of control (96.4 ± 3.5%). Contrarily, Adesanmi et al (2020) reported significantly ( P < 0.05) higher true digestibility (97.6%–98%) of diet/s comprising the blends of maize and almond (70:30) flours, which could be attributed due to the least amount of antinutritional factors in fermented/processed maize flour and almond.…”
Section: Resultsmentioning
confidence: 91%
“…The findings of Cajori (1921) demonstrated that pecan nut as the only source of dietary protein was not appropriate for rats and should be supplemented with some other proteins. Similarly, Adesanmi et al (2020) investigated the nutritional quality of blend/s of processed maize (70%) and almond seed (30%) flours as a sole source of diet in rats and observed substantially lower PER (0.58 ± 0.01–0.61 ± 0.01) as compared to control (1.30 ± 0.02). Previously, Shekib et al (2011) investigated the nutritional quality of two cultivars of Egyptian pecan nut and detected significantly ( P < 0.05) lower PER in experimental groups (approximately 2 ± 0.1) than that of control (2.2 ± 0.1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations